A comparison of equity crowdfunding in four countries: Implications for business angels1. (20th November 2017) - Tuomi, Krista; Harrison, Richard T.
Abstract: Equity crowdfunding as a rapidly growing source of finance for new and growing entrepreneurial ventures poses new challenges for financial regulators and potentially disrupts the early stage risk capital market and its existing actors, notably business angels. Equity crowdfunding responds primarily to the needs of small start‐ups that do not manage to access bank finance, or who do not need the larger sums available from venture capital or business angels. It is not appropriate for firms where business information is too sensitive to be shared with a large number of potential investors, nor those which require substantial amounts of follow on financing. Within these parameters and with sensible policy implementation and regulation, equity crowdfunding can play a useful complement to the role of business angels in innovation finance as an alternative form of start‐up and growth capital.